THE RELATIONSHIP BETWEEN SMOKING HABITS AND WORK STRESS AMONG BOARD OPERATORS IN ELECTRICITY COMPANIES: CROSS-SECTIONAL STUDY - Wardoyo, Dhea Aulia Hera; Wahyudiono, Yustinus Denny Ardyanto (Journal of Community Mental Health and Public Policy, 2024)
Background: The 2019 National Socio-Economic Survey showed that 92.1% of active smokers were workers. An increase in risky behaviour such as smoking can be a cause of stress in working individuals. Purpose: This study aimed to determine the strength of the relationship between smoking habits and occupational stress in board operators. Methods: This is a quantitative research design. The type of research used was observational with a cross sectional approach. Sampling using the total population of 52 people. The independent variable (smoking habit) was measured using the Penn State Nicotine Dependence Index and the dependent variable (work stress) was taken with the Workplace Stress Scale questionnaire. The strength of the relationship test was carried out with the contingency coefficient test to determine the strength of the relationship between variables. Results: 30 respondents (57.7%) do not smoke. While 30 respondents (57.7%) had work stress levels mostly in the moderate stress category. The results of the strong relationship showed c = 0.254 which means a weak relationship between smoking habits and occupational stress. Conclusion: Most of board operators do not have a smoking habit and experience moderate work stress and there is a weak relationship between smoking habits and work stress. Abstrak Latar Belakang: Survei Sosial Ekonomi Nasional 2019 menunjukkan sebanyak 92,1% perokok aktif berasal dari kalangan pekerja. Peningkatan perilaku berisiko seperti kebiasaan merokok dapat menjadi penyebab stres pada individu pekerja. Tujuan: Penelitian ini bertujuan untuk menentukan kuat hubungan kebiasaan merokok dengan stres kerja pada operator board. Metode: Ini adalah penelitian kuantitatif. Jenis penelitian yang digunakan adalah observasional dengan pendekatan cross sectional. Sampel menggunakan total populasi yaitu sebesar 52 orang. Variabel independen (kebiasaan merokok) diukur dengan menggunakan Penn State Nicotine Dependence Index dan variabel dependen (stres kerja) diambil dengan kuesioner Workplace Stress Scale. Uji kuat hubungan dilakukan dengan uji koefisien kontingensi untuk mengetahui kuat hubungan antar variabel. Hasil: 30 responden (57,7%) tidak merokok, sedangkan 30 responden (57,7%) tingkat stres kerja mayoritas dalam kategori stres sedang. Hasil kuat hubungan menunjukkan c = 0,254 yang memiliki makna hubungan lemah antara kebiasan merokok dengan stres kerja. Kesimpulan: Sebagian besar board operator tidak memiliki kebiasaan merokok dan mengalami stres kerja sedang serta terdapat hubungan lemah antara kebiasaan merokok dengan stres kerja.